Vitamin-E: Anti-Ulcer Activity; Beyond the Antioxidant Functions (Medical Forum Monthly, 2024)
Objective: To evaluate the anti-ulcer activity of vitamin-E on caecal ulcerogenicity of Diclofenac sodium in Albino rats.Study Design: A prospective experimental studyPlace and Duration of Study: Department of Anatomy, Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre Karachi during 2003.Materials and Methods: Diclofenac sodium and Vitamin-E were administered to Albino Rats separately and simultaneously at a dose of 2 mg/kg body weight (for each drug) orally once daily for two weeks. These animals were sacrificed, Caeca were identified and removed, opened along mesenteric border and examined under dissecting microscope for dilatation of the blood vessels, blood streaks and hemorrhagic areas. The caeca were fixed in 10% formalin, Embedded in paraplast, 4 um thick sections were cut on rotary microtome, stained with Haematoxylin and eosin stains. The histomorphological Features of caecal mucosa were compared with those in the control animals and analyzed statistically.Results: The study revealed that simultaneous use of vitamin-E administration with (NSAIDs) produced Anti-ulcer activity in caecal ulcers of albino Rats. Conclusion: The results suggest that vitamin-E produced anti-ulcer activity in Caecal ulcers of albino rats.